Analysis of Teacher Communication in Shaping Pancasila Class IV Profile Character - Ayu Saputri, Itha; Kaddas, Badruddin; Nurdiansyah, Erwin (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
Analysis of teacher communication in shaping the character of the Pancasila profile of grade IV, good moral values, character, and ethics in students. The purpose of this study is to shape a good personality in students such as honesty, respect for others, and good behavior in everyday life. This study is a qualitative study with a descriptive type of research. Teachers and students are involved as the main informants. Data collection techniques used include interviews, observation and documentation. Data analysis with data collection, data reduction, data presentation, and drawing conclusions. The results of the study show the reality of Pancasila profile character education. Character education in elementary schools helps shape character in the development of children’s morals, learning is carried out every day in class.